(untitled) (Research, Society and Development, 2022)
Introduction: The insula is a brain lobe that grows less during development and, therefore, is covered by the frontal, temporal and parietal lobes. Some of its functions are somatosensory processing, visceral information processing, interoception and empathy. Objective: Recognize the structure and functions of the insular cortex, as it is an area of the human cerebral cortex not yet fully understood. Methodology: This is a literature review, carried out in March 2022, in the following databases: National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (VHL), Virtual Health Library (VHL) and EBSCO Information Services. Results and Discussion: Current evidence suggests that the insula plays a strong role in conscious feelings by anticipating the body’s effects of emotional events. The insular cortex, activated by homeostatic imbalance, or by reward cues, plays a key role in this balancing process, so it is not surprising that the insula is heavily involved in addictive behaviors. In addition, an appropriate level of insular activity is required to provide a warning signal to initiate brain responses to salient stimuli. Conclusion: It is evident that the understanding of the anatomy and functionality of the insular cortex is essential for the elucidation of several neurosensory aspects of the human being, since the insula is functionally heterogeneous, with distinct patterns of connectivity with large-scale brain networks associated with numerous functions and behaviors.